Surgical Outcomes and Prognostic Factors in Cervical Cancer: A 12 year, Single-center Experience - Tanitra Tantitamit; Suttha Hamontri (Asian Pacific Journal of Cancer Biology, 2017)
Objective: This study was conducted to evaluate the surgical outcomes of patients with early-stage cervical cancer and to identify clinicopathological factors that may predict a 5-year disease-free survival of patients who are treated with modified or radical hysterectomies and pelvic lymphadenectomy. Methods: The record of 146 patients with early-stage invasive cervical carcinoma who had been treated at the HRH Princess Maha Chakri Sirindhorn Medical Center, in the period between January 2003 and December 2014 were retrospectively reviewed. Clinical and pathological variables that include age, wait time to surgery, stage of cancer, pelvic nodule status, lymphovascular space invasion, histology, depth of invasion, tumor grade, surgical margin status, parametrium involvement, and tumor size were recorded. The Kaplan-Meier statistical method was used for the calculation for the 5-year disease-free survival and the 5-year overall survival. The Log-rank test and Cox regression analysis were used to assess the significant factors relating to recurrence. Result: A Large population in this study was in Stage IB1 (62%). The most common histology obtained was of squamous cell carcinoma (68%). Approximately 77% of the patients underwent either a modified or radical hysterectomy and 25% had received adjuvant treatment. The median time of patient follows up was 60 months. The estimated 5-year disease-free survival of the patients with early-stage cervical cancer was 84%. Recurrent disease occurred in 14% of the patients and the majority of these (71%) were localized metastases. Stage, nodular status and tumor size were significant as poor prognostic factors resulting from the univariate analysis study. However, there were no statistically significant associations between these factors and the 5-year DFS on multivariable analysis. Conclusion: Early stage cervical cancer patients treated at our institute had favorable outcomes. The significant prognostic factors for disease-free survival were the stage, nodular status, and tumor size.